Model Perilaku Partisipasi Masyarakat Mengelola Bank Sampah Berbasis Kepercayaan dan Keterlibatan Sebagai Pemoderasi - Paramita Lea Christanti; Abdul Haris; Agung Nugroho Jati; Oki Kuntaryanto; Anis Marjukah; Arif Julianto Sri Nugroho; Moch Suranto (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to conduct a multivariate test of dependent variables on the social entrepreneurial behavior of Troketon residents managing a garbage bank influenced by three independent variables in the form of attitude, subjective norm and perceived behavioral control with trust and involvement as a moderator. The research object as a sample is residents of Troketon Pedan who run village garbage bank businesses as many as 120 respondents. The analysis used in the research was in the form of respondent item validity and reliability test, CFA test, variable regression test used moderation which were used to provide a perception picture in the public minds regarding proving the social entrepreneurial behavior model of Troketon residents related to garbage bank entrepreneurship. Quantitative test used AMOS 21 software. The test results obtained fit model. The findings are the attitude variable model test, perceived behavioral control influence the social entrepreneur behavior of residents, while a subjective norm variable has no significant effect. Two moderating variables, namely trust dan involvement, strengthen significantly the effect of the independent variable on the dependent variable. From the findings of the proven model, a strategy is needed for stakeholders to devise efforts to further increase the knowledge and confidence of local entrepreneurs managing a garbage bank towards increasing the competitiveness of social entrepreneurs in Troketon Village residents through the increase of income and welfare of micro-enterprises.